2018
DOI: 10.7475/kjan.2018.30.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Modeling on Health-related Quality of Life among Patients with Thyroid Cancer

Abstract: The aim of the study was to create a structural model based on Wilson and Cleary's Conceptual Model of Patient Outcomes. Secondly, the intention was to identify variables influencing the health-related quality of life (HRQoL) as reported by patients with thyroid cancer. Methods: A total of 201 patients with thyroid cancer were recruited from an outpatient clinic. Data were collected from June to November, 2015, using a structured questionnaire. The questionnaire included the Quality of Life-Thyroid Scale, Thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Thus, if family support and self-efficacy are higher, the degree of cancer adaptation is higher. Social support was shown to affect cancer adaptation in a previous study on thyroid cancer [20], while the current study reflects that cancer adaptation is positively correlated with family support and its amount. In a study by Park et al [21], the grade of anxiety and depression was significantly higher in female patients than it was in male patients, and they found that emotional temperament could cause emotional disorders.…”
Section: Discussionsupporting
confidence: 39%
“…Thus, if family support and self-efficacy are higher, the degree of cancer adaptation is higher. Social support was shown to affect cancer adaptation in a previous study on thyroid cancer [20], while the current study reflects that cancer adaptation is positively correlated with family support and its amount. In a study by Park et al [21], the grade of anxiety and depression was significantly higher in female patients than it was in male patients, and they found that emotional temperament could cause emotional disorders.…”
Section: Discussionsupporting
confidence: 39%
“…There is no universally accepted definition of home care. According to the literature [11], home care is a professional nursing service that employs all nursing processes and targets members of the whole family and family subsystems with varying degrees of health. The goal is to help the family system and its members achieve optimal health.…”
Section: Related Workmentioning
confidence: 99%
“…As a result of this study, it was found that symptom experience and health promotion had a direct effect on the quality of life of colorectal cancer surgery patients, and self-efficacy and social support had an indirect effect, and these variables explained 58.7% of the quality of life of colorectal cancer surgery patients. This is somewhat lower than the explanatory power of the quality of life model, which was 63% to 69%, respectively, in the study results of gastric cancer patients [ 34 ] and thyroid cancer patients [ 10 ]. It was found that there was a difference according to the influencing factors.…”
Section: Discussionmentioning
confidence: 82%
“…This study is based on the health-related quality of life model of Wilson and Cleary [ 4 ] and previous studies [ 9 , 10 ]. This study established a hypothetical model by synthesizing the influencing factors that explain the quality of life of patients with colorectal cancer surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation